PEMETAAN PENELITIAN MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR PENDIDIKAN JASMANI TAHUN 2013-2015 - Sriawan dan Nur Sita Utami (Jurnal Pendidikan Jasmani Indonesia, 2015)
AbstractThe purpose of this study was to determine the description of the students’ research (Thesis) mapping of TeacherPhysical Education for Elementary School Study Program in 2013-2015. The meta analysis of the data was usedto analyse samples in the form of research (thesis) abstract of 400 students of Teacher Physical Education forElementary School Study Program in 2013-2015. The samples consisted of 130 abstracts in 2013, 232 abstracts in2014, and 38 abstracts in 2015. Incidental sampling was used as the sampling collecting technique. The researchersas human instrument employed documentation guideline to collect the data. The data collection technique was doneby documentation. The data were analyzed by quantitative data percentage. The results showed that: the surveymethod used in the thesis 84.50% research (thesis); students as the samples at 69.75% research; and tests wereused as data collection techniques at 48.75% research.Keywords: Research (Thesis), Mapping, Abstract.AbstrakTujuan penelitian ini adalah mengetahui gambaran pemetaan penelitian (Skripsi) mahasiswa Prodi PGSD Penjas padatahun 2013-2015. Meta analisis data digunakan untuk mengaji sampel yang berupa 400 abstrak skripsi mahasiswaPGSD Penjas. Sampel terdiri atas 130 abstrak tahun 2013, 232 abstrak tahun 2014, dan 38 abstrak tahun 2015.Insidental sampling digunakan sebagai teknik pengambilan sampel. Peneliti sebagai human instrument menggunakanpedoman dokumentasi untuk mengumpulkan data. Teknik pengumpulan data dilakukan secara dokumentasi. Datadianalisis secara persentase data kuantitatif. Hasil penelitian menunjukkan bahwa: metode survei digunakan pada84,50% penelitian; siswa sebagai sampel pada 69,75% penelitian; dan tes digunakan sebagai teknik pengambilandata pada 48,75% penelitian.Kata Kunci: Skripsi, Pemetaan, Abstrak.